Stanislav Preprek – visonary librarian (Libellarium: journal for research in the field of information and related sciences, 2021)
Purpose. The aim of this paper is to present the significant contribution of Stanislav Preprek, composer, conductor, organist, poet, translator, librarian, teacher and scholar, to the development of librarianship and overall cultural life in Petrovaradin.Approach/methodology. The research included the reading of already published publications about the life and work of Stanislav Preprek, as well as reports on the work of the Library in Petrovaradin, their comparative analysis and drawing basic theses and conclusions, in order to present his contribution to the development of librarianship in Petrovaradin.Findings. The paper considers the engagement of Stanislav Preprek as a librarian and organizer of numerous cultural events in the library in Petrovaradin, in the post-war period, when it renewed its activities in difficult conditions.Originality. The paper contributes to the history of librarianship and points to the deserving employees, visionaries, and initiators in this field, one of them undoubtedly being Stanislav Preprek.Keywords: Library in Petrovaradin, Novi Sad City Library, Stanislav Preprek
Keywords: Library in Petrovaradin; Novi Sad City Library; Stanislav Preprek